On the Approximation of Functions of the Hölder Class by Biharmonic Poisson Integrals - Zhyhallo, K. M.; Kharkevych, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We determine the exact value of the upper bound of the deviation of biharmonic Poisson integrals from functions of the Hölder class.